Molecular detection of toxoplasma gondii DNA in goats (Capra hircus), sheep (Ovis aries), and donkey (Equus asinus) milk using PCR in East Azerbaijan province, Iran. (20th December 2022) - Deljavan, Naeimeh; Moosavy, Mir-Hassan; Hajipour, Nasser
Abstract: Toxoplasmosis, a zoonotic infection that is significant for public health (immunocompromised patients, pregnant women) and veterinary medicine (economic losses in the herd), is caused by an intracellular protozoan parasite belonging to the phylum Apicomplexa called Toxoplasma gondii . Consumption of unpasteurized milk and contaminated undercooked meat is a significant source for humans. The present study aimed to determine Toxoplasma gondii DNA in sheep, goats and donkeys Milk kept in East Azerbaijan province using the PCR method based on the B1 gene. For this purpose, 100 milk samples, including 45 sheep, 45 goats and 10 donkeys, were collected from different regions of northwestern Iran using direct milking and then transferred to the Food and Aquatic Health Laboratory under refrigerated conditions. The results showed that out of 100 milk samples examined, 16 samples (16%) were contaminated, and Toxoplasma gondii DNA was detected in 5 (11.11%) sheep, 9 (20%) goats and 2 (20%) donkeys milk specimen, respectively. These findings indicated that Toxoplasma gondii contaminated the raw milk, a human infection source. Highlights: Reporting the presence of T. gondii in milk of goat, sheep and donkey in Iran. The results demonstrate the presence of the DNA of T. gondii in buffalo, cow and camel's milk. Consumption of raw milk of different animals can be a risk factor for human health. To prevent infection with T. gondii, it is recommended to boil milk before consumption.